The Influence of Regional Original Revenue and Balancing Funds on the Human Development Index of Regencies/Cities in Indonesia - Pidhegso, Achmad Yugo; Hariyanti, Dini; Simanjuntak, Lydia Rosintan (Dinasti Publisher, 2025)
This study aims to examine and analyze the influence of Regional Original Revenue (PAD) and Balancing Funds namely the General Allocation Fund (DAU), the Special Allocation Fund (DAK), and the Revenue Sharing Fund (DBH) on the Human Development Index (HDI) in Indonesia. The data in this study cover all regencies/cities in Indonesia from 2016 to 2022. The research method used is panel data regression. The results show that PAD, DAU, DAK, and DBH simultaneously affect the HDI. Partial test results indicate that PAD, DAK, and DBH have a significant positive influence on HDI, while DAU has a significant negative effect. Based on these findings, local governments are encouraged to evaluate the use of DAU in efforts to improve HDI nationwide, considering that the utilization of DAU is at the discretion of the respective local governments.